2003
DOI: 10.1021/bi030034u
|View full text |Cite
|
Sign up to set email alerts
|

Solution Conformation of the Antibody-Bound Tyrosine Phosphorylation Site of the Nicotinic Acetylcholine Receptor β-Subunit in Its Phosphorylated and Nonphosphorylated States

Abstract: Phosphorylation of the acetylcholine receptor (AChR) seems to be responsible for triggering several effects including its desensitization and aggregation at the postsynaptic membrane and probably initiates a signal transduction pathway at the postsynaptic membrane. To study the structural and functional role of the tyrosine phosphorylation site of the AChR beta-subunit and contribute to the in-depth understanding of the structural basis of the ion channel function, we synthesized four peptides containing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Zhou and Abagyan calculated the binding energy of phosphotyrosine-containing peptides to SH2 and PTB domains [17]. Several molecular dynamics [1830] and homology modeling [27,31,32] studies have been reported involving phosphorylated proteins [1820,24,25,31–33] or peptides [21–23,26,27,34]. A Car-Parinello study has been reported [35], as well as a creative application of docking algorithms to investigate conformational changes upon phosphorylation of the N-terminal tail in phenylalanine hydroxylase [36].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou and Abagyan calculated the binding energy of phosphotyrosine-containing peptides to SH2 and PTB domains [17]. Several molecular dynamics [1830] and homology modeling [27,31,32] studies have been reported involving phosphorylated proteins [1820,24,25,31–33] or peptides [21–23,26,27,34]. A Car-Parinello study has been reported [35], as well as a creative application of docking algorithms to investigate conformational changes upon phosphorylation of the N-terminal tail in phenylalanine hydroxylase [36].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou and Abagyan calculated the binding energy of phosphotyrosine-containing peptides to SH2 and PTB domains [17]. Several molecular dynamics [18][19][20][21][22][23][24][25][26][27][28][29][30] and homology modeling [27,31,32] studies have been reported involving phosphorylated proteins [18][19][20]24,25,[31][32][33] or peptides [21][22][23]26,27,34]. A Car-Parinello study has been reported [35], as well as a creative application of docking algorithms to investigate conformational changes upon phosphorylation of the N-terminal tail in phenylalanine hydroxylase [36].…”
Section: Introductionmentioning
confidence: 99%
“…After phosphorylating a protein in silico, we need to explore the new energy landscape and identify the new global energy minimum, if in fact it is significantly different than that of the unphosphorylated protein. In principle, molecular dynamics could be used for this purpose, and in some cases, this type of strategy has been successful, in studies by ourselves and others [18][19][20][21][22][23][24][25][26][27][28][29][30]. However, the timescales for converting from the nonphospho to the phosphorylated form are unknown, and in fact are not physically meaningful because the in silico phosphorylation is alchemical, i.e., we do not attempt to mimic a kinase actually performing the phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…(13)(14)(15)(16) Although the mechanism of this modification is unknown, at least two possibilities exist: re-arrangement of disulfide bonds (17) and phosphorylation. (18,19) ECRG2 belongs to the kazal family which contains the conservative pattern x(8)-C-x(6)-C-x(7)-C-x(6)-Yx(3)-C-x(2,3)-C-x(17)-C, and these conservative cysteines are involved in three disulfide bonds. (20) The last cysteine located on c-terminal sequences was synthesized as immunogen for generating MAbs, so this cysteine may be involved in the formation of disulfide bond loop.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility for the alteration of MAb epitopes involves phosphorylated modification which will regulate nearly every aspect of cell life including protein folding, solubility, antigenicity, half-life, localization, and cell-to-cell interactions. (18,19) Bio-information analysis predicted that there is a serine phosphorylation site ser73 located on c-terminal of ECRG2 peptide, and these findings raised the possibility that the differential use of common phosphorylation sites in or near MAb epitopes or occupation of unique phosphorylation sites might contribute to the alteration of MAb reactivity.…”
Section: Discussionmentioning
confidence: 99%